Factors Associated with Exclusive Breastfeeding Practice In Adolescent Mothers, North Kalimantan, Indonesia - Reza Bintangdari Johan; Teresia Suminta Rotua Situmorang; Mufdlilah Mufdlilah; Nur Indah Noviyanti; Dessy Hertati (Placentum: Jurnal Ilmiah Kesehatan dan Aplikasinya, 2025)
The breastfeeding period is the golden age for babies as growth and development take place. In reality, there are still mothers who do not breastfeed their children. Adolescent mothers are more prone to stop breastfeeding their babies because adolescent mothers are not yet able to make decisions about feeding their babies. The study aimed to determine the factors that influence exclusive breastfeeding among adolescent mothers. Design study was Analytic observational with a cross-sectional approach. This study involved 106 adolescent mothers. The sampling technique used cluster random sampling according to the inclusion criteria. The instrument used a questionnaire. The study was conduct in the working area of Pantai Amal and Mamburungan Primary Health Center for two months. Data analysis using kendal-tau b. Adolescent mothers who provide exclusive breastfeeding amounted to 56.6%. There was a relationship between support, knowledge, perception, exposure to information sources about breast milk and formula milk, and socio-culture with breastfeeding in adolescent mothers (p-value